THE INFLUENCE OF LEARNING AWARENESS AND COGNITIVE ABILITY ON STUDENT ACHIEVEMENT - Epi Supriyani Siregar (FKIP Universitas Al Washliyah Medan, 2018)
This article examines the effect of mediating student learning awareness on cognitive abilities in improving academic achievement. This article discusses the role of teacher-student relationship variables and learning evaluation in encouraging the emergence of student learning awareness at the elementary school level. The data used are primary data, collected from 135 grade 5 and 6 teachers in 17 elementary schools in the Medan Polonia area, Medan City, Indonesia. Data analysis of Structural Equation Modeling (SEM) shows that there is a positive influence on the relationship and evaluation of learning on student achievement through learning awareness and cognitive abilities with a significant correlation (p < 0.05). This article's findings indicate that students' awareness of learning is a mediation that affects the improvement of cognitive abilities and academic achievement of students in the classroom.